Konsepsi Tentang Kebijakan Hukum Terbuka (Open Legal Policy) Pembentuk Undang-Undang Pasca Putusan Mahkamah Konstitusi Nomor 62/Puu-XXII/2024: Analisa Terhadap Pembatasan Kekuasaan Sebagai Inti Dari Paham Konstitusionalisme - Delfina Gusman (LPPM Universitas Ekasakti, 2026)
Constitutional Court Decision Number 62/PUU-XXII/2024 which granted the request for judicial review of the 1945 Constitution of the Republic of Indonesia regarding the presidential threshold (threshold for nominating President and Vice President) stated in the provisions of Article 222 of Law Number 7 of 2017